Fibrinolysis with Lower Dose Urokinase in Patients with Complicated Parapneumonic Effusion - Seul Lee; Heock Lee; Dong Hyun Lee; Bo Hyoung Kang; Mee Sook Roh; Choohee Son; Sung Hyun Kim; Hyun-Kyung Lee; Soo-Jung Um (Tuberculosis and Respiratory Diseases, 2021)
Background Intrapleural urokinase is one of the most widely used fibrinolytic agents in the treatment of complicated parapneumonic effusion (CPPE). However, little research has been performed on the optimal urokinase dosage. The aim of this study was to evaluate the treatment efficacy of half dose urokinase compared with conventional dose urokinase. Methods We retrospectively enrolled 92 patients with CPPE or empyema who underwent intrapleural urokinase treatment at two tertiary hospitals. Patients received antibiotics, chest tube drainage, and other treatments as part of routine care. The primary outcome was the treatment success rate in the half dose urokinase group (50,000 IU daily for maximal 6 days) and the conventional dose urokinase group (100,000 IU daily). Treatment success was defined as clinical and radiological improvements without surgical treatment or re-admission within one month. Results Forty-four patients received half dose urokinase, whereas 48 patients were treated with conventional dose urokinase. Both groups were relatively well matched at baseline, excluding higher serum white blood cell count and higher empyema prevalence in the half dose urokinase group. The treatment success rate was not different between the two groups (p=0.048). There were no differences in the rate of in-hospital death and surgical treatment, hospitalization duration, and indwelling catheter duration. In the multivariate analysis, urokinase dose was not a predictor of treatment success. Conclusion Half dose intrapleural urokinase is equally effective conventional dose urokinase in treating patients with CPPE or empyema.